PENINGKATAN KESEHATAN MENTAL MELALUI OLAHRAGA - Muhammad Rizki Firdaus; Desty Endrawati Subroto; Muhammad Dzakwan Alamsyah; Farid Rizki Hakiki; Nasrul Nasrul; Dini Permata Sari (Jurnal Padamu Negeri, 2025)
Mental health is very important in human life to carry out daily activities. The purpose of this study was to determine the benefits of exercise in improving mental health based on a systematic literature review. The study used the Systematic Literature Review (SLR) method. The database used to search for literature is data found on the Google Scholar website. The results of the study are presented by looking at the quality of the documents in detail and according to the scope of the study. There are 6 relevant articles from 25 related articles. Based on the search results according to the Preferred Reporting Items for Systematic Review and Meta Analyses (PRISMA) stages, exercise can improve mental health. The types of documents searched for in this study are documents with a time span of the last 10 years published in national journals indexed by Sinta and can be accessed openly. Based on the results and discussion, the conclusion of this study states that exercise can improve mental health.